Hubungan Jenis Kelamin, Usia, dan Pekerjaan dengan Kejadian Anemia pada Pasien Tuberkulosis Paru di Rumah Sakit Umum Daerah Abdul Moeloek Bandar Lampung pada Bulan Januari - Agustus 2022 - Fathunnisa, Ridha Riano; Sangging, Putu Ristyaning Ayu; Utami, Winda Trijayanthi; Soleha, Tri Umiana (CV. Jasa Sukses Abadi, 2026)
Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis and is classified as a chronic multisystem infection with diverse clinical manifestations. Hematological abnormalities are frequently observed in tuberculosis patients and are generally associated with non-immunological mechanisms. Anemia is one of the most common abnormalities. All chronic infections, including tuberculosis, can induce anemia through various pathogenic pathways. However, most studies indicate that suppression of erythropoiesis mediated by inflammatory factors plays a major role in the development of anemia in tuberculosis patients. This study aimed to describe the characteristics of anemia and identify factors associated with its occurrence in patients with pulmonary tuberculosis. An observational analytic study with a cross-sectional design was conducted. Data were obtained from the medical records of pulmonary tuberculosis patients with anemia at the Medical Records Unit of RSUD Dr. H. Abdul Moeloek Bandar Lampung from January to December 2022. A total of 85 patients who met the inclusion criteria were included and analyzed using univariate and bivariate analyses with the Chi-Square test. Univariate analysis showed that most patients had normocytic normochromic anemia, accounting for 66 patients or 77.6%, while microcytic hypochromic anemia was observed in 19 patients or 22.4%. Anemia was more common in male patients, with a proportion of 74.1%. Bivariate analysis demonstrated a significant association between age and anemia occurrence, with a p value of 0.024. No significant association was found between occupation and anemia or between sex and anemia. This study concludes that age is the only factor associated with anemia among pulmonary tuberculosis patients at RSUD Dr. H. Abdul Moeloek Bandar Lampung.